LEADING COMMODITY DEVELOPMENT STRATEGY ORTICULTURAL FRUIT CROPS IN PADANG PARIAMAN DISTRICT - Fhadil Alamsyah; Syahrial Syahrial; Ilham Maratadona (Universitas Perjuangan Tasikmalaya, 2023)
Horticultural Commodities are agricultural commodities that have high economic value and enormous agribusiness potential to be developed. This research aimed to analyze fruit commodities as leading commodities in Padang Pariaman Regency and formulate commodity development strategies to plant superior horticultural fruit in Padang Pariaman Regency. The method used is the Location Quotient (LQ), Specialization quotient (KS), and localization quotient (KL) to identify leading sectors and leading commodities, as well as SWOT analysis to formulate horticultural fruit crop development strategies. The results of this study showed that the leading fruit commodities consist of guavas, papayas, and mangoes. Therefore, the right strategy was needed to manage horticultural fruit crops through government policies that were right on target for developing these leading sector areas.